Value based education in Kenya: An exploration of meanings and practices - Wamahiu, Sheila; Ministry of Education Science and Technology; Women Educational Researchers of Kenya (Nairobi Ministry of Education, Science and Technology, 2016)
Contributed articles presented at a seminar.
Includes preface in Hindi.
Keywords: Education -- Moral and ethical aspects -- India; Education -- Aims and objectives -- India